Acute effects of heated resistance exercise in female and male power athletes - Casadio, J. R.; Storey, A. G.; Merien, F.; Kilding, A. E.; Cotter, J. D.; Laursen, P. B. (European Journal of Applied Physiology, 2017)
Purpose: To determine the effects of heated resistance exercise on thermal strain, neuromuscular function and hormonal responses in power athletes. Methods: Sixteen (n = 8 female; 8 male) highly trained power athletes completed a combined strength and power resistance exercise session in hot (HOT ~30 °C) and temperate (CON ~20 °C) conditions. Human growth hormone (hGH), cortisol and testosterone concentrations in plasma, peak power (counter-movement jump, CMJ) and peak force (isometric mid-thigh pull) were measured before and after each training session; thermoregulatory responses were monitored during training. Results: Skin temperature, thermal sensation and thermal discomfort were higher in HOT compared with CON. Sweat rate was higher in HOT for males only. Compared with CON, HOT had trivial effects on core temperature and heart rate. During HOT, there was a possible increase in upper-body power (medicine ball throw) in females [3.4% (90% CL -1.5, 8.6)] and males [(3.3% (-0.1, 6.9)], while lower-body power (vertical jump) was enhanced in males only [3.2% (-0.4, 6.9)]. Following HOT, CMJ peak power [4.4% (2.5; 6.3)] and strength [8.2% (3.1, 13.6)] were enhanced in female athletes, compared with CON, while effects in males were unclear. Plasma hGH concentration increased in females [83% (18; 183)] and males [107% (-21; 444)] in HOT compared with CON, whereas differential changes occurred for cortisol and testosterone. Conclusion: Heated resistance exercise enhanced power and increased plasma hGH concentration in female and males power athletes. Further research is required to assess the ergogenic potential of resistance exercise in the heat.